Mitsugumin 53 drives stem cell differentiation easing intestinal injury and inflammation - Yumeng Pei; Meng Fang; Hong-Kun Wu; Qionghua Cui; Li Quan; Xiaochuan Li; Keyi Zhang; Peng Xie; Peng Jiang; Yuan Liu; Meimei Huang; Fengxiang Lv; et al. (Signal Transduction and Targeted Therapy)
Abstract Emerging evidence suggests that priming intestinal stem cells (ISCs) towards secretory progenitor cells is beneficial for maintaining gut homeostasis against inflammatory bowel disease (IBD). However, the mechanism driving such biased lineage commitment remains elusive. Here we show that MG53, also named as TRIM72, prompts ISCs to secretory lineages via upregulating peroxisome proliferator-activated receptor α (PPARα), thus maintaining intestinal epithelium integrity against noxious insults. Using genetic mouse models, we found that MG53 deficiency leads to exacerbated intestinal damage caused by various injuries in mice, whereas MG53 overexpression in ISCs is sufficient to ameliorate such damage. Mechanistically, MG53 promoted asymmetric division of ISCs to generate more progenitor cells of secretory lineages via activating PPARα signaling. Specifically, MG53 overexpression induced PPARα expression at transcriptional level and concomitantly increased PPARα activity by elevating the contents of a panel of unsaturated fatty acids in the intestine that serve as potent endogenous agonists of PPARα. Furthermore, genetic ablation or pharmacological inhibition of PPARα abolished the protective effects of MG53. These findings reveal a crucial role of MG53-PPARα axis in driving the secretory lineage commitment of ISCs, especially during injury response, highlighting the important therapeutic potential of targeting MG53-PPARα signaling for IBD treatment and marking PPARα agonists as novel therapies for IBD caused by various etiologies.